The Effect of Adding Barley Flour (Setaria italica L.) on Sago Cookies Products (Metroxylon Sp.) as an Innovation in Local Food Products - Putri Ainurrohmah Sobari; Khairiah Khairiah; Sakina Yeti Kiptiyah (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2023)
This study aims to determine the effect of adding barley flour (Setaria italica L.) to sago cookies (Metroxylon Sp.) as an innovation in local food products. The design experimental used in this study was a Completely Randomized Design (CRD) with four formulation and four replications. The research parameters consisted of organoleptic properties using five scales and chemical analysis, including moisture, ash, fat, protein, carbohydrate, and crude fiber. Data were analyzed using the Analysis of Variance (ANOVA) statistical analysis; the values were significantly different between the sample, followed by Duncan's with a level of 5%. The results obtained from this study were that adding barley flour to sago cookies had a significant effect on aroma, texture, taste, and overall, while color had no significant effect. The formulation that received the highest rating from the panelists was cookies with a formulation with 60% sago starch and 40% barley flour. The study indicated that adding barley flour to sago cookies increased the water, ash, fat, protein, and crude fiber content but decreased total carbohydrate. The average chemical characteristics results of sago cookies with the addition of barley flour showed a moisture content 3.33 - 6.58 %, ash 2.31 - 2.79 %, fat 15.78 - 18.48 %, protein 4 .64 - 9.91 %, total carbohydrate 62.23 - 73.93 % and crude fiber 6.94 - 10.23 %. The best cookies with a formulation of 60 % sago starch and 40 % barley flour.